COVID-19 vaccination-related autoimmune hepatitis—a perspective - Sergi, Consolato M. (Frontiers in Pharmacology, 2023)
Autoimmune hepatitis (AIH) is an inflammation of the liver with clear-cut interface hepatitis and piecemeal necrosis located at the boundary between portal areas and periportal hepatocytes and characterized by autoimmunity to hepatocytes with increase of antinuclear antibody. After the disastrous SARS-CoV-2 pandemic flagellated several countries, several vaccines have been commercialized and become a ground for social responsibility. The mRNA vaccines, issued by Pfizer-BioNTech (BNT162b2) and Moderna (mRNA-1273), do not use prebuilt viruses to supply the antigen in the subject's body, are not perfect, but have been useful in tackling the pandemic.Nevertheless, both myocarditis and autoimmune hepatitis have been reported as side effects of the vaccination programs in addition to thromboembolic events. Here we explore this topic and give a data-based perspective gathering a comparison between the Titin protein of the sarcomeric and myocarditis. The isolation of a Drosophila gene using serum from a patient with autoimmune scleroderma recognized an epitope on chromosomes (condensed mitotic form) in both human cultured cells and early Drosophila embryos. It revealed that this gene encodes a Drosophila homologue of the vertebrate titin (D-Titin). Moreover, anti-Titin antibodies have been found in a subset of patients with myasthenia gravis, a neuromuscular junction disease that is mostly associated with autoimmune antibodies, such as anti-acetylcholine receptor-antibody.Co-existence of myasthenia gravis and autoimmune hepatitis is rare, and a cohort of patients with myasthenia gravis anti-Titin antibodies seem to be highly relevant.